Neuromuscular training programs for the injury prevention in young athletes. A literaturereview - Robles-Palazón, F.; Sainz de Baranda, P. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2017)
The aims of this review are: (1) describing the principal lower extremity injury prevention programs in young athletes that have a demonstrated efficacy, whose prevention have been destined for ball team sports, do not require any additional material for their application and the duration allows for their implementation as previous warm-upprograms; and (2) analyzing the advantages and disadvantages of the prevention strategies according to their possibility of implantation in the regular sport practice. For this purpose, a total of 5 neuromuscular injury prevention programs were selected. Although all the programs have shownpositive effects in terms of the reduction of sport injury incidence, the detailed analysis of the characteristics of the prevention strategies recommend the utilization of the FIFA 11+ and Knäkontroll programs for their greater adaptability to the application context and their facility for the implementation in the regular sport practice.